KONTRIBUSI LEARNING CULTURE DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PNS DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING - Ahadul Mondi; Eka Risma Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze the influence of learning culture and the physical work environment on employee performance, with job satisfaction as a moderating variable at the Pariaman City Department of Agriculture, Food, and Fisheries. The study employed a quantitative approach involving 114 employees consisting of civil servants (PNS), PPPK employees, and outsourced cleaning service workers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all research instruments met the validity and reliability criteria, and the research model demonstrated good predictive capability. Hypothesis testing revealed that learning culture and the physical work environment have a positive and significant effect on employee performance. However, job satisfaction was not found to moderate the relationship between learning culture and performance, nor between the physical work environment and performance. These findings suggest that improving employee performance can be more effectively achieved through strengthening a learning culture and enhancing the physical work environment directly. Future studies are recommended to explore other variables that may influence performance and to examine job satisfaction as a mediating variable.Keywords: Learning Culture, Physical Work Environment, Civil Servant Performance, Job Satisfaction